William L. Petersen, Tatian’s Diatessaron, its Creation, Dissemination, Significance, and History in Scholarship, Supplements to „Vigiliae Christianae" 25, Leiden - New York - Köln 1994, E. J. Brill, ss. 555. - Woźniak, Jerzy (Vox Patrum, 2000)
review